Exchange rate uncertainty and import prices in the euro area - Boris Blagov (Review of International Economics, 2019)
This paper analyzes the effects of exchange rate uncertainty on the pricing behavior of import firms in the euro area. Uncertainty is measured via the volatility of the structural shocks to the exchange rate in a nonlinear vector-autoregressive model framework and is an important determinant of import prices. An increase in exchange rate uncertainty is associated with a fall in prices on average, which suggests that the exchange rate risk is borne by the importers. Controlling for the origin of imports (within or outside the euro area) is important for assessing the impact of exchange rate movements on prices.
Keywords: 330